Fenomena Cyborg dan Lenyapnya Sifat Feminis: The Cyborg Phenomenon and the Disappearance of Feminine Traits - Siti Raudhatul Jannah (An-Nisa’ Journal of Gender Studies, 2011)
Technological advances allow us to create robots that can be studied from psychological and social perspectives as a unified set of actions. The goal is to mimic the highly complex brain so that these robots can become truly intelligent. Robots will never be the same as humans, due to the simple fact that humans have random thought processes and often make mistakes. Machines cannot be forced to think in the same patterns as humans. On the other hand, cyborgs, a cybernetic mechanism, a combination of machine and organism, a creation of social reality and also fictional imagination, are now increasingly existent. In America, 10% of the population is currently estimated to be “cyborgs” in the technical sense. That is, people who use electronic pacemakers, artificial joints, drug implantation systems, corneal lens implants, artificial skin. In turn, cyborgs exist within social reality, living within social relationships, even political structures. Feminist thinker Donna Haraway observes that the cyborg myth holds the potential for radical political action, much like the freedom feminists seek in finding common ground with one another. Aspek teknologi memungkinkan kita menciptakan robot-robot yang dapat dipelajari melalui perspektifpsikologi dan sosial sebagai kesatuan fungsi tindakan. Tujuannya untuk meniru otak yang sangat rumit sehingga robot-robot iersebut bisa menjadi benar-benar pintar. Robot takkan pernah menjadi sama seperti manusia, dikarenakan fakta sederhana bahwa manusia memiliki proses berpikir yang acak dan sering membuat kesalahan. Mesin tak bisa dipaksa untuk berpikir dengan pola yang sama seperti manusia. Di sisi lain, cyborg, sebuah mekanisme sibernetik, suatu perpaduan antara mesin dan organisme, ciptaan dari realitas sosial dan juga rekaan fiksi, kini kian eksis. Di Amerika, 10% dari populasinya saat ini diperkirakan adalah "cyborg" dalam arti teknis. Yaitu orang-orang yang menggunakan elektrorik pacemaker, tulang sendi tiruan, sistim implantasi obat, impan lensa kornea, kulit tiruan. Pada gilirannya, cyborg ada dalam realitas sosial, hidup dalaт hubungan sosial, bahkan konstruksi politik. Tokoh feminis Donna Haraway melihat bahwa mitos cyborg memiliki potensi untuk melakukan tindakan politik yang radikal sebagaimana kebebasan yang dimiliki para femnis mencari kesamaan satu sama lain.